GE_GERICHTE P/930/2013 vom 23. Dezember 2020 - GE Cour de justice (2020)
DROIT D'OBTENIR UNE DÉCISION;PRINCIPE DE LA CÉLÉRITÉ;CLASSEMENT IMPLICITE;DISJONCTION DE CAUSES | CPP.319; CP.251; CPP.322; CPP.30; Cst.29